Internal Conflicts in Joe Penna’s Stowaway - Katarina Imas; I Made Perdana Skolastika (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2025)
This study investigates the internal conflicts experienced by the main characters in Joe Penna’s Stowaway, focusing on Zoe Levenson, David, and Commander Bernadette. The research aims to identify the types of internal conflict and analyze how these conflicts influence character development and the narrative. Employing a qualitative method with observational techniques, the film was repeatedly viewed to record significant dialogues, expressions, and behaviors indicating inner struggles. Data were analyzed using Freud’s psychoanalytic theory (1923), Tajfel and Turner’s Social Identity Theory (1979), Kant's (1785) ethical perspectives from deontology and consequentialism. The findings reveal three main internal conflicts: Zoe’s moral dilemma between saving a life and ensuring crew safety, David’s struggle between personal research investment and collective survival, and Bernadette’s leadership responsibility versus self-sacrifice. These conflicts reflect the tension between moral values, professional identity, and survival instincts in an isolated environment. The study concludes that internal conflicts shape individual decision-making and drive the film’s emotional and ethical complexity.